The Fear of the Expression of Face - the Voice "into the Boundaries" of Philosophy of Emmanuel Levinas. - Jaranowski, Marcin (Filozofia Chrześcijańska, 2009)
The main purpose of the article is to supplement the philospohy of Emmanuel Levinas with the conception of fear. The analysis of certain expressions used in the works of Levinas leads the author to the conclusion that the ethical relation to the face of the Other causes irreversable changes in the self. Jaranowski considers two types of reaction to nakedness (Levinas describes the face of the Other as “naked”) and puts emphasis on the negative one – nakedness is something that should not be exposed, it causes anxiety. The question of nakedness casts light on the problem of the call from the Other as a kind of interruption. For one can not predict all the consequences of responding to the call from the face of the Other. Finally author claims that there is a kind of fear that has its subject in moral obligation as such.